Information System of Teacher Assignment Journal in Wooi State Junior High School - Rakhmadi, Aris; Yusrifa, Khumaila Masfarina (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
The teaching journal recording system is a document of evidence of teaching implementation that can guarantee the quality and quantity of the learning process. Wooi State Middle School, Wonawa District, Yapen Islands Regency, Papua still records teaching journals manually by handwritten. The aim of this research is to develop a teacher assignment journal information system as a solution to the problems experienced by Wooi State Middle School in the form of scattered journal summaries. This system development uses prototyping and implementation using HTML, PHP, CSS, Javascript, MySQL, and the CodeIgniter Framework. Research has produced a journal information system that provides website-based journal recording and recording features. The research used the Blackbox testing method to test all available features, and this method stated that everything worked well. The system also passed testing using the System Usability Scale (SUS) method which resulted in a score of 74.62, which means it is acceptable.